2018
DOI: 10.18203/2349-2902.isj20181114
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of postoperative chronic pain after tension free inguinal hernia repair using absorbable versus non absorbable sutures for mesh fixation

Abstract: Background: Inguinal hernia is a one of common diagnosis which is frequently encountered in routine clinical practice. The Lichtenstein technique (tension free mesh repair) is currently the gold standard in open inguinal hernia repair. Currently chronic groin pain (Inguinodynia) is one of the common complications after hernia repair and it may affect quality of life and it has been reported in 16% to 62% of the patients.Methods: This prospective, randomized study was conducted in the department of general surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…As compare to other studies Group B was statistically significant. 1,9,11,13 Kim-Fuchs et al Paajanen et al, Jeroukhimov et al, Kharadi et al Paajanen et al Paajanen et al found the incidence of chronic pain in Group A and in Group B was statistically not significant. 2,3,8,10,12,20 In our study incidence of chronic pain in group A (n=40) at 3 month was 1.27 and 1.06 in group B (n=40) with p value 0.048.…”
Section: Early Complicationsmentioning
confidence: 98%
“…As compare to other studies Group B was statistically significant. 1,9,11,13 Kim-Fuchs et al Paajanen et al, Jeroukhimov et al, Kharadi et al Paajanen et al Paajanen et al found the incidence of chronic pain in Group A and in Group B was statistically not significant. 2,3,8,10,12,20 In our study incidence of chronic pain in group A (n=40) at 3 month was 1.27 and 1.06 in group B (n=40) with p value 0.048.…”
Section: Early Complicationsmentioning
confidence: 98%
“…13 Meena et al study mean age group in group A was 45.4 years while in group B was 46.5 years, which are comparable. 4 Paajanen et al study mean age group in group A was 53 years while in group B was 53 years with p=0.679, which was not statistically significant. 13 1 Jenaw et al study mean post-operative pain score in group A was 0.30±0.65 while in group B was 0.08±0.27 with p value=0.045, which was statistically significant.…”
Section: Discussionmentioning
confidence: 84%
“…Study results concluded that absorbable suture material does not appear to cause less neuropathic pain than nonabsorbable sutures [ 12 ]. In a contrary study by Meena et al, it was concluded that absorbable sutures for mesh fixation had less groin pain as compared to nonabsorbable sutures in hernia repair, with 155 participants in each group [ 14 ].…”
Section: Discussionmentioning
confidence: 99%